Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2) is associated with immune phases of patients with chronic hepatitis B - Fan, Yu-Chen (Oncotarget, 2017)
Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2) is a newly negative immune regulator but its role in different immune phases of patients with chronic hepatitis B (CHB) is unknown. We determined the mRNA levels of TIPE2, interleukin-6, interleukin-10, tumor necrosis factors-α and interferon-γ in peripheral blood mononuclear cells from 205 naïve treated CHB patients and 15 healthy controls by quantitative real time polymerase chain reaction. Intrahepatic TIPE2 protein was also determined using immunohistochemistry staining. The TIPE2 mRNA level in CHB patients was significantly higher than that in healthy controls. Moreover, the TIPE2 mRNA level in immune clearance (IC) phases was significantly higher than that in immune tolerance (IT) phase; whereas TIPE2 mRNA in HBeAg negative hepatitis (ENH) was obviously higher than low replication (LR) phase. Furthermore, the optional cut off values of 2.02 and 1.59 for TIPE2 mRNA level have strong power in identifying IC and ENH from IT and LR. In addition, intrahepatic TIPE2 protein was predominantly located in hepatocyte plasma and correlated with hepatic inflammatory and fibrosis. Multivariate analysis showed tumor necrosis factors-α, interferon-γ and HBV DNA load were independently correlated with TIPE2 level. In conclusion, TIPE2 might be associated to the immune clearance of patients with chronic hepatitis B.